The Role of Private Equity Investments in Public Firms : International Evidence - Dahiya, Sandeep; Klapper, Leora; Parthasarathy, Harini; Singer, Dorothe (World Bank, Washington, DC, 2015)
This paper compares the raising of external equity capital from private equity investors via private investments in public equity (PIPEs) and seasoned equity offerings (SEOs) using a sample of 456 PIPEs and 1,910 SEOs drawn from nine Asian countries. Consistent with the idea that insiders attempt to time the markets, firms issuing SEOs are preceded by a significantly higher run-up in stock price compared with those issuing PIPEs. This result is consistent with the undervaluation hypothesis that states that firms are more likely to issue PIPEs when they perceive their stock to be undervalued. In contrast to the United States where this undervaluation appears to be driven by financial distress and asymmetric information, the results show PIPE and SEO issuers to be statistically undistinguishable from each other. The announcement of a PIPE offering is on average associated with a significantly higher stock market reaction compared with an issue of a SEO, suggesting that private equity investors may play a certification or monitoring role. However, a comparison of PIPE issuers' operating performance and stock market returns in the pre-issue and the post-issue periods does not detect any significant improvements.